2011
DOI: 10.1039/c1lc20020h
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired, efficient, artificial lung employing air as the ventilating gas

Abstract: Artificial lungs have recently been utilized to rehabilitate patients suffering from lung diseases. However, significant advances in gas exchange, biocompatibility, and portability are required to realize their full clinical potential. Here, we have focused on the issues of gas exchange and portability and report a small-scale, microfabricated artificial lung that uses new mathematical modeling and a bio-inspired design to achieve oxygen exchange efficiencies much larger than current devices, thereby enabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 19 publications
(28 reference statements)
0
101
0
Order By: Relevance
“…Challenges associated with scaling of microfluidic oxygenator devices have been addressed in a recent review 23 , and have been debated in subsequent communications. 24–25 Most reports of microfluidic oxygenators have been limited to blood flow rates of 5 mL/min or less; 17, 18, 21, 2629 one has reported blood flow rates as high as 40 mL/min, but the oxygen content of the blood appeared to drop below commercial oxygenator oxygen transfer levels (5 volume percent oxygen relative to the total blood volume) above 10 mL/min blood flow rates. 30 Another recent report from Rieper et al has demonstrated blood oxygen transfer at blood flow rates as high as 60 mL/min, clearly a major advance over most of the microfluidic literature [T. Rieper, C. Muller and H. Reinecke, However, this report does not describe an approach to ensure that blood flow patterns in the channel structures are designed in a manner to avoid sharp corners and non-physiologic and potentially deleterious flow paths.…”
Section: Resultsmentioning
confidence: 99%
“…Challenges associated with scaling of microfluidic oxygenator devices have been addressed in a recent review 23 , and have been debated in subsequent communications. 24–25 Most reports of microfluidic oxygenators have been limited to blood flow rates of 5 mL/min or less; 17, 18, 21, 2629 one has reported blood flow rates as high as 40 mL/min, but the oxygen content of the blood appeared to drop below commercial oxygenator oxygen transfer levels (5 volume percent oxygen relative to the total blood volume) above 10 mL/min blood flow rates. 30 Another recent report from Rieper et al has demonstrated blood oxygen transfer at blood flow rates as high as 60 mL/min, clearly a major advance over most of the microfluidic literature [T. Rieper, C. Muller and H. Reinecke, However, this report does not describe an approach to ensure that blood flow patterns in the channel structures are designed in a manner to avoid sharp corners and non-physiologic and potentially deleterious flow paths.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a need for an advanced artificial lung (AL) arises as a bridge-to-transplant, that is, during the waiting period prior to lung replacement surgery. Indeed, patients with severe respiratory disabilities that require whole lung transplant must usually wait for over a year until a donor is found [9]. For such cases, a long-term solution is needed: a stable and permanent AL that can improve life quality and reduce mortality while awaiting transplant [10, 11].…”
Section: Artificial Lungsmentioning
confidence: 99%
“…Microfabricated systems also allow for easier prediction and control over flow parameters, including shear stresses created during blood flow within the device. Indeed, computational fluid dynamics (CFDs) are commonly used to carefully design the delicate architecture of a microfluidic AL device [9, 10, 12, 14]. …”
Section: Artificial Lungsmentioning
confidence: 99%
“…Early pioneering efforts explored the use of microfluidic techniques to fabricate microchannel networks for blood flow and oxygenation 9–11 . More recently, several groups have reported the development of prototype devices for clinical applications including cardiopulmonary support for acute lung failure in the ICU and portable oxygenators for wearable pulmonary support for COPD patients 1214 .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with existing hollow fiber cartridge systems, microfluidic technologies can provide smoother blood flow pathways and transitions at branching points, thinner gas transfer membranes with dimensions that are closer to the actual alveolar membrane thickness, and shallow channels that improve oxygen transfer by reducing the distance between the oxygen source and the blood. Most efforts to date have explored the performance of 2D planar structures comprised of a single blood flow network layer and a gas source layer sandwiching a gas transfer membrane 13,14 . Clinical devices will likely require expanding this geometry into a third dimension to provide sufficient oxygen transfer at physiologically acceptable levels of fluid mechanical resistance for clinical scale blood flows.…”
Section: Introductionmentioning
confidence: 99%